Cause and Impact Analysis of Homeless and Beggars: A Study of Urban Poverty and Social Stigma in Medan - Redemptus Benediktus; Dionisius Meritus (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2022)
This study proposes an in-depth analysis of the factors causing and impacting the phenomenon of homeless people and beggars in the city of Medan. The aim of the research is to identify the root causes as well as the social consequences of these problems in the urban context. Research methods include qualitative and quantitative data analysis, including interviews with the individuals involved, community surveys, and related statistical analyses. The results of the analysis show that high unemployment rates and economic inequality are central factors in pushing individuals towards a state of homeless people and beggars. Limited access to education and health services also plays an important role in maintaining this problem. Social factors, such as family problems and violence, also have a large impact on individual conditions. The impact of the problem of homeless people and beggars includes higher physical and mental health risks, as well as social stigmatization that hinders community reintegration efforts. The existence of homeless people and beggars can also affect the city's image, security, and economic aspects. By understanding the root of the problem and its impact, it is hoped that this research will contribute to efforts to reduce homeless people and beggars in Medan City and develop a more inclusive and caring society